Implementasi Google For Education (GAFE) pada SDIT Al-Ittihad Rumbai untuk Optimalisasi Pembelajaran Daring - Lestari, Indah; Shumaya Resty Ramadhani; Ridha, Muhammad Arif Fadhly; Listiyanti, Dwi (Universitas Nusantara PGRI Kediri, 2022)
Several external factors such as the occurrence of disasters and the COVID-19 pandemic have limited learning activities in schools so that they must be carried out online. Teachers need to socialize how to use technology for online learning classes and schools must provide support for that. Therefore, in this community service,